Enhancing English Reading Comprehension of EFL Undergraduate Students through Narrative Texts - Jittisukpong, Pisith; Thomas Barling, Gavin (Journal of Roi Et Rajabhat University, 2026)
This study aimed to: 1) investigate the extent to which narrative texts enhance reading comprehension among first-year students at a private university in Bangkok, and 2) explore students’ attitudes toward learning to read through narrative texts. The participants were 25 first-year students at the Thai-Nichi Institute of Technology. Narrative texts were implemented with the participants over a period of 10 weeks. The research instruments included identical English reading comprehension tests administered as pretest and posttest, and a reading attitudes questionnaire. The data were analyzed using mean scores, standard deviation, and a dependent samples t-test. The results indicated that narrative texts significantly improved students’ reading comprehension. The posttest scores were significantly higher than the pretest scores (p < .01). In addition, most students demonstrated positive attitudes toward learning English reading through narrative texts.